Strategi Jurnalisme Online Pada Media Sosial Tiktok @InfoBandungKota - Dewanti, Sinta; Astuti, Dyah Rahmi; Faizin, Barzan (Jurusan Ilmu Komunikasi, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Djati Bandung, 2025)
This study aims to elaborate the online journalism strategy on Info Bandung Kota tiktok account through Paul Bradshaw’s BASIC principles that cover brevity, adaptability, scannability, interactivity, and community and conversation. This research uses an interpretive paradigm, with a qualitative approach. The method used in this research is descriptive method with data collection techniques. The results of this study reveal that the online journalism strategy on @infobandungkota tiktok include the following points: First, strategies for Brevity through duration summarization and caption writing. Second, strategies for adaptability using language selection and choosing the type of music that is tailored to the characteristics of the audience. Third, the strategy to Scannability is by using catchy headlines and footage, as well as the use of hastags that match the content of the news. Fourth, strategies to Interactivity is by using the viral events and content outside of journalism that influences journalistic content. Fivth, strategies to create Community and Conversation by using group forum, tiktok features, and replying to audience comments.